KONFLIK RUMAH TUHAN: - Khamami Zada (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Conflicts related to houses of worship in some regions in Indonesia have indicated a tension between the majority and minority groups. The minority found it difficult to build a house of worship, for the majority opposed it. While an attempt of resolution was initiated by the central and regional government including community elites. However, conflict settlements had not always been successful although it was resolved through legal process and mediation. The conflict of GKI Yasmin in Bogor, for instance, was one example that legal process was not effective to resolve the conflict. Similarly, the conflict of mushalla As-Syafi’iyah in Denpasar was also another case where a mediation process with the involvement of local leaders also failed. However, a conflict of temple establishment in Tanjung Pinang showed a successful resolution by a mediation involving the religious leaders and the local government elites. This paper suggests that the resolution of conflicts pertinent to the cases of houses of worship depends favorably on the initiatives taken by the local government and the local religious leaders.